Restless legs syndrome prevalence in patients on chronic hemodialysis in central Serbia - Nikić Petar M.; Andrić Branislav R.; Stojanović-Stanojević Marina; Đorđević Verica; Petrović Dejan; Stojimirović Biljana B. (Vojnosanitetski Pregled)
Background/Aim. Restless legs syndrome (RLS) is a sensorymotor disorder and the core feature of this syndrome is a distressing, irresistible need or urge to move the legs. RLS is one of the most troublesome conditions experienced by endstage renal disease patients treated with regular hemodialysis, and is significantly associated with their increased mortality. The aim of this study was to assess the prevalence of RLS in the patients with end-stage renal failure in the three dialysis centers in central Serbia, and to investigate the association of the syndrome with clinical characteristics and biochemical variables. Methods. A cross-sectional multicentric study in which 166 consecutive hemodialysis patients were evaluated using a standard questionnaire based on diagnostic criteria elaborated by the International Restless Legs Syndrome Study Group was performed. All patients were reinterviewed and clinically examined by a qualified neurologist. The data on the patients with and without RLS were compared. Results. The prevalence of RLS was 22.96% (95% CI, 16.57% to 29.35%). There was no significant difference in duration of hemodialysis and clinical characteristics when we compared the patients with RLS with those without RLS. We found significantly higher levels of blood urea nitrogen and creatinine and lower level of Kt/V index in the patients with RLS, which might point to inadequate dialysis in these patients. Conclusion. In our study the prevalence of RLS in the patients on the regular hemodialysis was 22.96%. The obtained results are similar to those of other studies using the same methodology in the white population on the regular hemodialysis.